Adolescents understanding of poverty and the poor in rural Malaysia - Murnizam Halik; Webley, Paul (Elsevier, 2011)
The aim of this research was to explore Malaysian adolescents’ perception of poverty and the poor. The data consisted of 79 semi-structured interviews with school children aged 12–13 and 15–16 years old from rural and urban areas in Sabah, Malaysia. According to them, poverty is mainly economic. Their responses about the causes of poverty can be categorised as individualistic, structural, fatalistic and other factors (such as age, geography, land and encouragement). Older respondents from rural and urban areas gave more individualistic and structural attributions compared to the younger respondents. While they believed that government is most responsible to help the poor, other parties such as the poor, public and NGO’s should also work together to alleviate poverty. They suggested that these parties can contribute in terms of donation, infrastructural improvement, education, attitudinal change and job opportunities. Respondents acknowledged that hard work and education are important to improve their standard of living. However, education is regarded as a ticket to seek their fortune elsewhere. These results emphasised the need for the Malay adolescents to learn about not being dependent on the government for employment in order to avoid mass urban migration in the near future.poor, public and NGO’s should also work together to alleviate poverty. They suggested that these parties can contribute in terms of donation, infrastructural improvement, education, attitudinal change and job opportunities. Respondents acknowledged that hard work and education are important to improve their standard of living. However, education is regarded as a ticket to seek their fortune elsewhere. These results emphasised the need for the Malay adolescents to learn about not being dependent on the government for employment in order to avoid mass urban migration in the near future.